Paving the way for nationally appropriate mitigation actions in the agricultural sector - Hänsel G (2012)
Key messages - Nationally appropriate mitigation actions (NAMAs) in the agricultural sector can be elements in the pathway to food security, green growth and sustainable development. - NAMAs can provide additional resources for climate-smart agriculture, where multiple benefits, including adaptation benefits, are generated alongside mitigation. - Mitigation and adaptation are often inseparable and complementary in meeting multiple goals. - NAMAs and national adaptation programmes of action (NAPAs) could be aligned to maximize synergies and co- benefits. - Land-based mitigation and adaptation measures should be integrated for implementation at subnational levels. - NAMAs require a proactive approach by developing countries and should build on existing planning processes, tools, and technologies. - The United Nations Framework Convention on Climate Change (UNFCCC) should encourage and enable a country-driven process for mitigation in agriculture. Moreover, developed countries must follow through on their commitments made under the Copenhagen Accord and Cancun Agreements to support mitigation actions in developing countries.